Upgrading Pengelolaan Sampah Mandiri: Implementasi Lodong Sisa Dapur Sebagai Metode Pengelolaan Sampah Organik Rumah Tangga Dusun Sawit, Desa Panggungharjo - Kristianingrum, Yuli Purwandari; Anthony, Juve (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Student Community Service-Community Empowerment Study of Gadjah Mada University (KKN-PPM UGM) is the application of knowledge and skills possessed by students to solve problems in society. The issue faced by the community is organic waste management in Panggungharjo Village, Sewon District, Bantul Regency. Independent organic waste management is necessary because waste management facilities in the village are not sufficient to manage the entire community waste. To address the issue, KKN-PPM UGM students from IV period YO-130 unit implemented kitchen waste composters and conducted waste segregation education program. Students collaborated with members of the PKK (Family Welfare Empowerment) and the Head of Sawit Hamlet. The community service programs that have been carried out results in community mindset and behavioral shift, as they are encouraged to recycle organic waste. Fertilizers obtained from the use of kitchen waste composters can increase community income through agricultural or trading activities. The implementation of kitchen waste composters also supports the achievement of the third and twelfth Sustainable Development Goals. Thus, the KKN-PPM UGM program contributes to solving the problem of organic waste management at the household level and has a positive impact on community welfare.